AWC thermosensory neuron interferes with information processing in a compact circuit regulating temperature-evoked posture dynamics in the nematode Caenorhabditis elegans. (March 2023) - Kano, Amane; Matsuyama, Hironori J.; Nakano, Shunji; Mori, Ikue
Abstract: Elucidating how individual neurons encode and integrate sensory information to generate a behavior is crucial for understanding neural logic underlying sensory-dependent behavior. In the nematode Caenorhabditis elegans, information flow from sensory input to behavioral output is traceable at single-cell level due to its entirely solved neural connectivity. C. elegans processes the temperature information for regulating behavior consisting of undulatory posture dynamics in a circuit including two thermosensory neurons AFD and AWC, and their postsynaptic interneuron AIY. However, how the information processing in AFD-AWC-AIY circuit generates the posture dynamics remains elusive. To quantitatively evaluate the posture dynamics, we introduce locomotion entropy, which measures bandwidth of the frequency spectrum of the undulatory posture dynamics, and assess how the motor pattern fluctuates. We here found that AWC disorders the information processing in AFD-AWC-AIY circuit for regulating temperature-evoked posture dynamics. Under slow temperature ramp-up, AWC adjusts AFD response, whereby broadening the temperature range in which animals exhibit fluctuating posture undulation. Under rapid temperature ramp-up, AWC increases inter-individual variability in AIY activity and the fluctuating posture undulation. We propose that a compact nervous system recruits a sensory neuron as a fluctuation inducer for regulating sensory-dependent behavior. Highlights: AWC induces and AFD inhibits the fluctuation in motor pattern. AWC broadens the temperature range where animals exhibit fluctuating motor pattern. AWC increases inter-individual variability in downstream AIY calcium responses. There is bidirectional communication between AFD and AWC. AFD evokes AWC, and AWC adjusts the range of temperature where AFD is activated.